2006
DOI: 10.1111/j.1349-7006.2006.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐dependent promotion of rat forestomach carcinogenesis by combined treatment with sodium nitrite and ascorbic acid after initiation with N‐methyl‐N′‐nitro‐N‐nitrosoguanidine: Possible contribution of nitric oxide‐associated oxidative DNA damage

Abstract: Dose-dependent promotion effects of combined treatment with sodium nitrite (NaNO 2 ) and ascorbic acid (AsA) on gastric carcinogenesis were examined in rats pretreated with N-methyl-N′ ′ ′ ′-nitro-N-nitrosoguanidine (MNNG). Groups of 15 6-week-old F344 male rats were given 0.01% MNNG in their drinking water for 10 weeks to initiate carcinogenesis in the glandular stomach and a single intragastric administration of 100 mg/kg/ bodyweight of MNNG by stomach tube at week 9 to initiate carcinogenesis in the foresto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…As several mechanisms of anti-carcinogenic effects of AA, anti-oxidant properties [13], the ability to react with nitrite as a prototype inhibitor of the nitrosation reaction [30], the regulatory role in transcription and translation [19,27,46] and cell-cycle arrest at the G 2 /M DNA damage checkpoint during oxidative stress [15] have been proposed. On the other hand, enhanced carcinogenic effects of AA have been described in several reports [12,20,36]. In the present study, the absolute and relative liver weights were significantly increased in the DEN+KA+AA group in comparison with the DEN alone group.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As several mechanisms of anti-carcinogenic effects of AA, anti-oxidant properties [13], the ability to react with nitrite as a prototype inhibitor of the nitrosation reaction [30], the regulatory role in transcription and translation [19,27,46] and cell-cycle arrest at the G 2 /M DNA damage checkpoint during oxidative stress [15] have been proposed. On the other hand, enhanced carcinogenic effects of AA have been described in several reports [12,20,36]. In the present study, the absolute and relative liver weights were significantly increased in the DEN+KA+AA group in comparison with the DEN alone group.…”
Section: Discussionsupporting
confidence: 66%
“…The anti-mutagenic, anti-clastogenic and anti-carcinogenic effects of AA [7,11,22,42] have been reported to be ascribed to several mechanisms, such as its anti-oxidant properties [13], the ability to react with nitrite as a prototype inhibitor of the nitrosation reaction [30], the regulatory role in transcription and translation [19,27,46] and cell-cycle arrest at the G 2 /M DNA damage checkpoint during oxidative stress [15]. On the other hand, in spite of the reports demonstrating that AA has anti-carcinogenic effects, it has been reported that AA enhanced the forestomach tumor-promoting activity of sodium nitrite in rats [36]. In addition, AA enhanced the rat urinary bladder carcinogenesis promotion activity of NaHCO 3 [20].…”
mentioning
confidence: 99%
“…13,34,35 Therefore, one of the underlying mechanisms is reduction of free radical scavenging oxidative damage. 36 In an in vitro system we could also show that canolol suppresses inflammation mediators (Fig. 5).…”
Section: Discussionmentioning
confidence: 82%
“…51 Dose-dependent promotion of rat forestomach carcinogenesis by combined treatment with sodium nitrite and ascorbic acid after initiation also showed a possible contribution of NOassociated oxidative DNA damage. 52 Schistosomal infection may also influence DNA methylation. It was shown that Schistosoma-associated urinary bladder tumors had more genes methylated than non-Schistosomal tumors, 53 and the extent of methylation in UCs was lower than in SCCs.…”
Section: Discussionmentioning
confidence: 99%